2004
DOI: 10.1016/j.susc.2003.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of benzene adsorption on the Cu(110) surface and simulation of STM images

Abstract: The adsorption of benzene molecules onto the Cu(110) surface has been studied using a crystalline linear combination of atomic orbitals approximation (LCAO).Adsorption energetics have been modeled at both the Hartree-Fock (HF) and density functional theory (DFT) level, and scanning tunneling microscope (STM) images generated for the preferred adsorption geometry. The calculated binding energies are strongly dependent upon basis set superposition errors (BSSE). As expected HF provides a relatively poor descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 41 publications
11
30
0
Order By: Relevance
“…As a preliminary test of the accuracy of our computational setup, we first calculated the energetically favored positions of a single benzene molecule on the Cu(110) surface. In agreement with the experiments [30,31] and previous theoretical calculations [39], we found that the benzene is chemisorbed between two rows of atoms along [110]-direction of the Cu(110) surface. The lowest adsorption energy (−0.401 eV) is obtained for the so-called long-bridge position where the benzene ring is on top of two Cu-atoms (see Fig.…”
Section: Theoretical Methodologysupporting
confidence: 92%
See 1 more Smart Citation
“…As a preliminary test of the accuracy of our computational setup, we first calculated the energetically favored positions of a single benzene molecule on the Cu(110) surface. In agreement with the experiments [30,31] and previous theoretical calculations [39], we found that the benzene is chemisorbed between two rows of atoms along [110]-direction of the Cu(110) surface. The lowest adsorption energy (−0.401 eV) is obtained for the so-called long-bridge position where the benzene ring is on top of two Cu-atoms (see Fig.…”
Section: Theoretical Methodologysupporting
confidence: 92%
“…All these molecular orbitals are π-type, and they arise from the combination of the p z -atomic type orbitals perpendicular to the molecular plane. When the benzene adsorbs on Cu(110) surface, there is a small charge transfer from the surface to the π * 2 and π * 3 orbitals, which become partially occupied [53,54]. Therefore, according to molecular orbital theory, the highest occupied molecular orbital of the tip will interact with the π * 2 , π * 3 , and π * 1 of the adsorbed benzene.…”
Section: Tip-benzene Interactions: a Frontier Molecular Orbital Theormentioning
confidence: 99%
“…Their on-top image shows also a high symmetry, and their bridge-A image is elongated along the same axis as our protrusion splitting. Although this protrusion splitting was not observed within TH limits, a similar feature was observed in a more recent theoretical study of benzene adsorbed on a Cu(1 1 0) surface [16].…”
Section: Adapted Stm Imagessupporting
confidence: 84%
“…[24] In the case of Ni-A C H T U N G T R E N N U N G (110), the preferred adsorption site of the benzene monomer is the hollow site and the resulting adsorption sites of 6P are different to those observed here on CuA C H T U N G T R E N N U N G (110). For benzene on Cu-A C H T U N G T R E N N U N G (110), both experiments [25] and theoretical calculations [26,27] have revealed that the long-bridge sites are preferred. In the case of 6P on the less reactive (2 1)-O surface, where the aromatic planes are tilted, the determination of the exact registry is more difficult, even though the periodicity is clear in the STM images.…”
Section: B)mentioning
confidence: 99%